FIRST FINDS OF CONODONTS IN PERMIAN AND TRIASSIC STRATA OF THE RUSHAN-PSHART REGION OF THE PAMIRS - Dronov V.I.; Bragin N.Yu. (My University, 1990)
One of us (V.I.D.) has been investigating the tectonics, stratigraphy and the age of the rocks of the Rushan-Pshart region since 1959. We refocused our research to siliceous beds, in the hope of finding radiolarians or conodonts. In the section of the Dunkel'dyk block totalling (at most) 4066 meters, conodonts were found at only two levels: near the base (?) of the Upper Permian and near the base of the Triassic, in rocks of the Indian stage. The conodonts from the latter level are diagnostic to the substage level and can even be assigned to particular conodont zones. The remaining parts of the section require further study in order to find fossil remains and determine their age.
Keywords: Triassic; Permian; Палеозой::Пермская; Paleozoic::Permian; Mesozoic::Triassic; Мезозой::Триасовая